Teachers’ Perception of the Quality Assurance and Skill Acquisition required from Office Technology and Management Students for National Development - Oluwalola, Felicia K.; Oyedeji, N. B.; Oyedele, J. F. (NIU Journal of Humanities, 2018)
The study examined the quality assurance and skill acquisition required by office technology and management students for national development. Two research questions titled â€˜What are the needs for quality assurance in office technology and management programme for national development and what are the necessary skills required of office technology and management students for national developmentâ€™  guided the conduct of the study. Descriptive survey research design was used for the study. A total of 38 business education lecturers in the public tertiary institutions in Kwara state were selected. A questionnaire with Cronbach reliability of 0.82 was the instrument used for data collection. Mean score and standard deviation was used to analyze the research questions. The result of the data collected and analyzed indicated among others that the need for quality assurance in OTM is to serve as indispensable component for quality control strategy and determine the level of adequacy of the facilities available for quality control in office technology and management programme. It was concluded based on the findings that there is the need for quality assurance in office technology and management programme. This will serve as indispensable component for quality control strategy and determine the level of adequacy of the facilities available for quality control in office technology and management programme. It was recommended among others that there is the need for constant and efficient supervision of the educational activities of office technology and management department by both internal and external supervisory bodies for efficient academic delivery.